Female undergraduates’ perception of mathematics: a mixed-methods study - Paudel, Tara; Dahal, Niroj; Hasan, Md. Kamrul (Frontiers in Education, 2025)
Mathematics is essential in daily life and career development, yet gender disparities persist, particularly in contexts such as Nepal, where socio-cultural norms influence educational access. This study examines the perceptions of female undergraduate mathematics students at Tribhuvan University, Nepal, exploring factors affecting their attitudes, self-efficacy, and motivation. A mixed-methods QUAN-QUAL research design integrated quantitative surveys (n = 75) and qualitative interviews (n = 4). Quantitative findings revealed that 72% of participants held negative attitudes toward mathematics, perceiving it as stressful (66%) and male-dominated (65%), with low self-efficacy (37% negative) and ambivalent motivation (49% uncertain). Caste/ethnicity significantly influenced perceptions of mathematics as male-dominated (χ2 = 23.923, p = 0.021). Qualitative insights highlighted socio-cultural barriers, including familial pressures prioritizing marriage over education, gendered stereotypes, and limited parental education. Female undergraduate students reported balancing household duties with academic demands, exacerbating stress and self-doubt. Despite recognizing mathematics use, systemic inequities hindered engagement. The study underlines the need for gender-sensitive curricula, confidence-building pedagogies, and community awareness to challenge stereotypes and enhance support. Recommendations include policy reforms, scholarships for marginalized groups, and teacher training to foster inclusive learning environments. Addressing these barriers is critical to transforming mathematics education into an equitable and empowering space for Nepali female students.